Productivity, taxes, and hours worked in Spain: 1970-2015 - Juan C. Conesa; Timothy J. Kehoe (SERIEs - Journal of the Spanish Economic Association, 2017)
In the early 1970s, hours worked per working-age person in Spain were higher than in the United States. Starting in 1975, however, hours worked in Spain fell by 40%. We find that 80% of the decline in hours worked can be accounted for by the evolution of taxes in an otherwise standard neoclassical growth model. Although taxes play a crucial role, we cannot argue that taxes drive all of the movements in hours worked. In particular, the model underpredicts the large decrease in hours in 1975-1986 and the large increase in hours in 1994-2007. The lack of productivity growth in Spain during 1994-2015 has little impact on the model's prediction for hours worked.
Keywords: C68; E13; E24; H31; 330; Dynamic general equilibrium; Hours worked; Distortionary taxes; Total factor productivity; Produktivitätsentwicklung; Steuerpolitik; Arbeitszeit; Neoklassisches Wachstumsmodell; Spanien